Organisational restructuring and institutional management: The case study of state-owned enterprise - Electricity of Vietnam - Tham, Huyen Anh (2007)
Electricity of Vietnam (EVN) is a large state-owned enterprise, which has been one of the most important growth engines of the Vietnam economy. As the country is in transition, institutional environments surrounding EVN undergo significant changes including cultural, social, political, economic and legal transformations. In response, EVN has implemented large-scale organisational restructurings but to what extent are EVNs strategies influenced by institutional pressures and to what extent can EVN exercise resistance to these forces? A large part of the answer lies in the management of institutional context at both organisational and individual levels. In this thesis, the author explores the process of institutional change in a different context to that of the West. The findings provide foundations for the discussion of a model of institutional linkages for EVN and discussion of theoretical developments.